Longer Duration of Untreated Psychosis is Associated with Poorer Outcomes for Patients with Delusional Infestation - Dmitry V. Romanov; Peter Lepping; Anthony Bewley; Markus Huber; Roland W. Freudenmann; Andrey Lvov; Stephen Bertel Squire; Eric O. Noorthoorn (Medical Journals Sweden, 2018)
We examined the association between the duration of untreated psychosis and outcome for patients with delusional infestation. This multi-centre international study included 211 consecutive patients. Illness severity was evaluated at first presentation and outcome was measured with the Clinical Global Impression scale (CGI) at baseline and follow-up. A regression analysis showed a clear clinical and statistically significant association between shorter duration of untreated psychosis and better outcome at follow-up. Patients with a duration of untreated psychosis of less than one year showed a CGI-S change from 5.37 to 2.07; those with a duration of untreated psychosis of 1-5 years a change from 5.48 to 2.59, and those with a duration of untreated psychosis of >5 years a change from 5.59 to 3.37. This difference of 1.1 CGI points between the groups resembles a clinically relevant difference in patient outcome. Our results suggest that longer duration of untreated psychosis in patients with delusional infestation is associated with significantly less favourable clinical outcomes.